PENILAIAN KINERJA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BONE - Hamid, Abdul; Arman, Agus; Suhendra, Suhendra; Nurmiati, Nurmiati; Lubis, Bastian (Patria Artha Journal of Accounting dan Financial Reporting, 2022)
This study aims to determine and analyze the financial performance of the Public Works and Spatial Planning Office of Bone Regency in 2018 - 2020. This study uses a value for money model which is a financial performance analysis tool for public sector organizations with ratios consisting of: economic ratios, efficiency ratio, and effectiveness ratio. The results showed that the Public Works and Spatial Planning Office in 2018-2020 based on the concept of value for money in general had shown good performance where the average economic ratio in 2018-2020 at the Bone District Public Works and Spatial Planning Service was 86, 61%, which means it is economical, then the average efficiency ratio is 90.90% which means it is efficient and the average effectiveness ratio shows a figure of 126.23% which means it is effective.